Estimates of the size distribution of meteoric smoke particles from rocket-borne impact probes - Antonsen, Tarjei; Havnes, Ove; Mann, Ingrid (Journal of Geophysical Research: Atmospheres, 2017)
An edited version of this paper was published by AGU. Copyright (2017) American Geophysical Union. Antonsen, T., Havnes, O. & Mann, I. (2017). Estimates of the size distribution of meteoric smoke particles from rocket-borne impact probes. Journal of Geophysical Research: Atmospheres, 12353-12365. https://doi.org/10.1002/2017JD027220 . Ice particles populating noctilucent clouds and being responsible for polar mesosphericsummer echoes exist around the mesopause in the altitude range from 80 to 90 km during polar summer.The particles are observed when temperatures around the mesopause reach a minimum, and it is presumedthat they consist of water ice with inclusions of smaller mesospheric smoke particles (MSPs). This workprovides estimates of the mean size distribution of MSPs through analysis of collision fragments of the iceparticles populating the mesospheric dust layers. We have analyzed data from two triplets of mechanicallyidentical rocket probes, MUltiple Dust Detector (MUDD), which are Faraday bucket detectors with impactgrids that partly fragments incoming ice particles. The MUDD probes were launched from Andøya SpaceCenter (69∘17’N, 16∘1’E) on two payloads during the MAXIDUSTY campaign on 30 June and 8 July 2016,respectively. Our analysis shows that it is unlikely that ice particles produce signiﬁcant current to thedetector, and that MSPs dominate the recorded current. The size distributions obtained from these currents,which reﬂect the MSP sizes, are described by inverse power laws with exponents of k ∼ [3.3 ± 0.7, 3.7 ± 0.5]and k ∼ [3.6 ± 0.8, 4.4 ± 0.3] for the respective ﬂights. We derived two k values for each ﬂight dependingon whether the charging probability is proportional to area or volume of fragments. We also conﬁrm thatMSPs are probably abundant inside mesospheric ice particles larger than a few nanometers, and the volumeﬁlling factor can be a few percent for reasonable assumptions of particle properties.